Pengaruh Store Atmosphere, Keragaman Produk, dan Harga Terhadap Impulse Buying Pada MR.DIY Lombok Epicentrum Mall - Septiani, Wiwinda; Rinuastuti, Baiq Handayani (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to test and analyze the influence of store atmosphere, product diversity and price on implude buying at MR.DIY Lombok Epicentrum Mall. The samples used in this study amounted to 100 samples with sampling techniques using non-probability sampling techniques with purposive sampling methods. The data analysis used multiple linear regression analysis using SPSS Statistic 20 software. The results of testing and data analysis show that the indicators in the study are declared valid where in the classical assumption test the data is normally distributed and multicollinearity does not occur. In this study, it was found that store atmosphere had an insignificant effect on impulse buying at MR.DIY Lombok Epicentrum Mall. While the Product Diversity and Price variable has a significant effect on impulse buying at MR.DIY Lombok Epicentrum Mall.